Colletotrichum menezesiae sp. nov.: a novel species causing anthracnose on chayote in Brazil - Dos Santos Vieira, Willie Anderson; Almeida Da Costa, Christiane; Paz Saraiva Câmara, Marcos; Michereff, Sami Jorge; Reis, Ailton (Phytotaxa, 2023)
A new pathogenic Colletotrichum species was isolated from chayote (Sicyos edulis) leaves and fruit presenting typical anthracnose symptoms from fields in Ibirité (Minas Gerais state) and Tijucas (Santa Catarina state), Brazil. The species Colletotrichum menezesiae sp. nov. is described and illustrated. Multilocus phylogenetic analyses based on combined ACT, GAPDH, nrITS and TUB2 partial sequences revealed that Colletotrichum isolates from chayote form a distinct clade within the C. orbiculare species complex. This clade does not contain the ex-type of any species previously described and is also recognized as an independent lineage according to the GCPSR criteria.